POLITISASI BIROKRASI LOKAL DALAM PEMILIHAN KEPALA DAERAH SECARA LANGSUNG - Lutfi Wahyudi (Jurnal Paradigma (JP), 2019)
This article discusses the politicization of bureaucracy in direct regional elections that occur in several regions in Indonesia. Analysis was carried out on several cases that occurred with cultural approaches. The findings are politicization of bureaucracy carried out by the pattern of patron-client relations between politicians and bureaucracy. Politicians need bureaucracy as a political machine, and bureaucracy needs the support of politicians as a means to develop careers. Practices related to patron-client relations such as persuasive action and the use of patronage are still the most important methods applied by local political actors in winning the contestation of regional head elections, while at the same time asserting that the main base of actors is to become legitimate political leaders and authoritative is economic resources and good social relations, both are the main elements of patron-client relations.Keywords: politicization, bureaucracy, patron-client, regional election